Phonologically similar, high-density targets to improve intelligibility: A single-case study in a Cypriot-Greek– speaking child with consistent phonological disorder - Petinou, Kakia; Filippou, Elma; Papastefanou, Theodora (My University, 2026)
Aim: To test whether training with phonologically similar, high–neighborhood-density word cohorts promotes expressive phonological gains in a 4-year-old bidialectal Cypriot-Greek–speaking child with a consistent phonological disorder. Method: A single-case study design with follow-up included baseline (pre-test), intervention, post-test, and one-month follow-up. Sixteen 45-minute sessions were delivered twice weekly over two months by treating clinicians; outcomes were scored by a second SLP blinded to phase and targets. Stimuli were organized into phonologically similar, high-density cohorts. Outcomes were obtained with a 49-item picture-naming probe; maintenance/generalization were assessed with 20 untreated items at follow-up. Dependent measures were Proportion of Consonants Correct (PCC), Whole-Word Matches (WWM), Phonetic Inventory Size (PIS), and phonological processes; the Intelligibility in Context Scale (ICS) was completed by the child’s teacher at baseline and follow-up. Results: Pre- to post-test analyses showed gains across all measures (PCC, WWM, PIS, and reduced processes). At follow-up, gains were maintained and generalized to untreated items, with improved ICS ratings. Conclusions: Implementing phonologically similar, high-density cohorts within a structured single-case intervention yielded clinically meaningful and maintained improvements in expressive phonology and functional intelligibility in Cypriot Greek. Findings contribute preliminary cross-linguistic support for neighborhood-density– informed target selection in SSD.